Intraoperative ultrasound for nonpalpable breast lesions – experience and operative time - Valentin Ivanov; Rossen Dimov; Blagoi Marinov; Valentin Ivanov; Desislava Tashkova (Folia Medica, 2023)
Introduction: The essential tools doctors need to diagnose breast cancer tumors at the early stages and with no clinical presentation are screening mammography and ultrasonography. Nonpalpable breast lesions are a current problem nowadays and there are various types of navigation techniques that are utilized in order to achieve cancer cell-free resection margins in the first place. Intraoperative ultrasound has been proven to be a safe and effective way to excise this type of breast tumors.Aim: To study the correlation between the experience we obtained while using intraoperative ultrasound for excision of nonpalpable breast lesions, and the duration of surgery. Materials and methods: Twenty-five women with nonpalpable breast lesions underwent breast-conserving surgery using ultrasound navigation. Nominal and ordinal data were presented using numbers and percentages. Spearman’s rank-order correlation was used to assess the effect of experience gained on the duration of surgery.Results: The tumor distribution was 72% malignant tumors and 28% benign. A 100% identification rate in the effective surgical excisions was reported. In the process of gaining experience using the method, the duration of surgery shortened by 30%. No tumor cells on ink were found in all specimens and there was no need for secondary surgeries.Conclusions: Our results demonstrate a relatively short learning curve, and we believe that breast surgeons should be helped and encouraged to gather adequate expertise to ensure patient safety and gain confidence.